The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1002/ajhb.22481
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration, quality, and timing and their associations with age in a community without electricity in haiti

Abstract: Average time in bed in this Haitian sample was greater than previously reported for industrialized countries like the United States (9.3 versus. 7-8 h);, however, actual sleep duration averaged only 7 h. No age-related decline in sleep duration or quality was observed in Haiti.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 31 publications
(40 reference statements)
1
40
2
Order By: Relevance
“…Importantly, adolescents in our study attended school in the morning, and school times were always during daylight hours; thus, students in neither community were exposed to electric light at school outside of natural daylight times. A recent study using actimetry in adults in a Haitian community without access to electricity suggested that, whereas the time in bed was longer than in more industrialized U.S. communities, sleep duration was not (Knutson, 2014). Wright and colleagues (2013) studied the sleep-wake cycle using actimetry and the phase of the circadian clock—assessed through melatonin release—in participants under typical conditions with access to artificial light and again in the same participants during a week-long camping trip under natural light conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, adolescents in our study attended school in the morning, and school times were always during daylight hours; thus, students in neither community were exposed to electric light at school outside of natural daylight times. A recent study using actimetry in adults in a Haitian community without access to electricity suggested that, whereas the time in bed was longer than in more industrialized U.S. communities, sleep duration was not (Knutson, 2014). Wright and colleagues (2013) studied the sleep-wake cycle using actimetry and the phase of the circadian clock—assessed through melatonin release—in participants under typical conditions with access to artificial light and again in the same participants during a week-long camping trip under natural light conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent anthropologic studies of people in societies with little or no electricity have failed to indicate that these people sleep more than people in industrialized societies [50, 51]. …”
Section: Discussionmentioning
confidence: 99%
“…Information on human sleep in settings without artificial (that is, electrically produced) light is accessible from historical and ethnographic records, along with a handful of more recent studies that more directly quantify sleep patterns . Worthman and Melby argued that, compared to their postmodern industrial counterparts, traditional societies are characterized by strikingly different sleep ecology and behavior.…”
Section: Investigating Unique Aspects Of Human Sleepmentioning
confidence: 99%